Distribusi Kecepatan Aliran di Saluran Terbuka Pada Permukaan Saluran Bergelombang - Saiful Rochdyanto (agriTECH, 1992)
Study on velocity distribution in wavy bed was conducted in a 10 m long, 0.5 m wide, 0.4 m depth glass-walled rectangular open channel. Flow characteristic was measured by hot wire anemometer and data was transferred to personal computer by digitizer. The Reynolds number which calculated from the maximum velocity are 3940,5630, 8190, and 12,930 respectively. Result of study shows that velocity data can not be approached by using the logarithmic law Mean while the power-law velocity distribution seems applicable in explaining the scanered velocity data. The velocity reduction about 0.21u/um in the area close to the bed and 0.05 u/um In the middle of turbulent boundary layer is disadvantage in the view point of hydraulic structure operation